2014
DOI: 10.1016/j.pneurobio.2013.09.002
|View full text |Cite
|
Sign up to set email alerts
|

Controversies and evolving new mechanisms in subarachnoid hemorrhage

Abstract: Despite decades of study, subarachnoid hemorrhage (SAH) continues to be a serious and significant health problem in the United States and worldwide. The mechanisms contributing to brain injury after SAH remain unclear. Traditionally, most in vivo research has heavily emphasized the basic mechanisms of SAH over the pathophysiological or morphological changes of delayed cerebral vasospasm after SAH. Unfortunately, the results of clinical trials based on this premise have mostly been disappointing, implicating so… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
267
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 319 publications
(272 citation statements)
references
References 488 publications
(555 reference statements)
5
267
0
Order By: Relevance
“…28,29 Both of them usually develop brain edema, which is a major independent risk factor for death and a poor outcome after SAH. 30 Both neuronal apoptosis and BBB rupture were observed at 24 hours after SAH in our present work, which may be the cause of increased brain water content. Further researches were in urgent need to explore a key factor in the development of apoptosis in brain research.…”
Section: Strokesupporting
confidence: 54%
“…28,29 Both of them usually develop brain edema, which is a major independent risk factor for death and a poor outcome after SAH. 30 Both neuronal apoptosis and BBB rupture were observed at 24 hours after SAH in our present work, which may be the cause of increased brain water content. Further researches were in urgent need to explore a key factor in the development of apoptosis in brain research.…”
Section: Strokesupporting
confidence: 54%
“…[4][5][6][7][8] Theoretically, these post-hemorrhagic cascades and products may contribute to further vascular ischemia and neuronal injury. [9][10][11] High mobility group box 1(HMGB1) is a nuclear factor that has been identified as an important immune mediator, triggering the production of various inflammatory cytokines in many diseases.…”
Section: Introductionmentioning
confidence: 99%
“…[3][4][5] In both animal and clinical studies, the severity of bleeding and the extent of decreased CBF correlated with neurological outcome [6][7][8] ; however, how and to what extent the initial global ischemia or subsequent elevated ICP contribute to early brain injury remains poorly understood. [3][4][5] A feasible way to reduce elevated ICP is decompressive craniectomy (DC), a technique that dates back more than a century. 9 In recent years, both animal and clinical studies reported beneficial effects of DC for treating conditions, such as traumatic brain injury 10,11 and malignant middle cerebral artery (MCA) infarction.…”
mentioning
confidence: 99%